APLIKASI SILASE TOTAL CAMPURAN HIJAUAN SKALA LAPANGAN : PENGARUH SILASE TOTAL CAMPURAN HIJAUAN DENGAN PENAMBAHAN BAKTERI ASAMLAKTAT (Lactobacillus plantarum) DAN LEVEL MOLASSES BERBEDA TERHADAP KINERJA DOMBA EKOR TIPIS - , ARIF STYAWAN, Prof. Ir. Zaenal Bachruddin, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aimedwas to determine the performance of a thin tail sheep (TTS) fed total mixture forage silage with different levels of molasses and Lactic Acid Bacteria inoculant (Lactobacillus plantarum). Fiftenmale of TTS weighing 23 Â± 3 kg were divided into three treatment and each treatment consisted of 5 sheep as replication. Treatment I with addition of L.plantarum and without the addition of molasses (T0), treatment II with L.plantarum + 1 % molasses (T1) and treatment III with L.plantarum + 2 % molasses (T2) . Forage used comose of rice straw, corn straw , king grass , peanut straw and gliricidia. Feeding was done 2 times a day ( morning and afternoon ). All animal within treatment were fed by pollard with the same amount and given before total mixture forage silage feeding during the experiment. The research design used was completely randomized design pattern Oneway (ANOVA). Analysis of variance for ADG, feed intake and feed conversion and further with DMRT test. The variables measured were feed intake ( dry matter intake and consumption of crude protein ) , TDN intake , weight gain and, feed conversion ratio, feed cost per gain. Statistical analysis showed that there was no real difference between T0 , T1 and T2 in dry matter intake (DM), crude protein (CP), total digestible nutrients (TDN), ADG and feed conversion and feed cost per gain T0, T1, T2 each one (14.242,50 vs 19.294,94 vs 21.093,98). It can be concluded that the addition of molasses on total mixture forage silage was not yet to improve the performance of a TTS.